Carbon nanofiber aerogel and preparation method thereof

By introducing polymers in the preparation process of carbon aerogels to form additional crosslinking points, the problem of insufficient mechanical properties and stability of carbon aerogels is solved, and its mechanical properties and conductivity are significantly improved. It is suitable for many fields. high performance material applications.

CN119430152AActive Publication Date: 2025-02-14SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411541142.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing carbon aerogels have weak mechanical properties and stability, and have poor electrical and thermal conductivity, which limit their application in high-performance materials in many fields.

Method used

Carbon nanofiber aerogel was prepared by mixing the bacterial cellulose dispersion containing inorganic ammonium salt with the polymer solution, freezing and freeze-drying, and then pyrolyolysis treatment. The polymer forms additional physical or chemical crosslinking during carbonization, increasing the crosslink density between carbon nanofibers.

Benefits of technology

It significantly improves the structural stability and mechanical properties of carbon nanofiber aerogels, enhances its electrical and thermal conductivity, provides a high specific surface area, is conducive to adsorption or catalytic reactions, and is not prone to deformation when subjected to external pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430152A_ABST
    Figure CN119430152A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano materials, in particular to carbon nanofiber aerogel and a preparation method thereof.The preparation method of the carbon nanofiber aerogel comprises the steps that bacterial cellulose dispersion liquid containing inorganic ammonium salt and a polymer solution are mixed to obtain mixed dispersion liquid, the mixed dispersion liquid is subjected to freezing treatment, and after freeze drying, the carbon nanofiber aerogel is obtained; the bacterial cellulose aerogel is obtained; and carrying out pyrolysis treatment on the bacterial cellulose aerogel to obtain the carbon nanofiber aerogel. The polymer is introduced in the preparation process, extra carbon can be generated in the carbonization process, connection between carbon nanofibers is tighter, the overall structural strength of the material is enhanced, through a composite carbon network formed after the polymer is carbonized, the carbon content of the aerogel is increased, and through the crosslinking and filling effects, the thermal conductivity of the aerogel is improved. The mechanical property of the aerogel is improved. A high-strength carbon network can better disperse stress, and collapse or excessive deformation of the structure is avoided when the aerogel bears external force, so that the maximum compression strength of the aerogel is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano material preparation, and in particular to a carbon nanofiber aerogel and a preparation method thereof. Background Art

[0002] As a cutting-edge material, carbon aerogel has many advantages. Carbon aerogel has rich microporous and mesoporous structures, and its carbon-based network structure exhibits good conductivity and excellent mechanical properties. It can withstand certain pressure and deformation, has good stability in high temperature environments, and shows great potential in many fields.

[0003] After bacterial cellulose is pyrolyzed, cellulose nanofibers are converted into carbon nanofibers to form carbon aerogels with a three-dimensional cross-linked network structure. However, due to the fewer cross-linking points of carbon nanofibers inside the aerogel after pyrolysis, its mechanical properties and stability are weak. Fewer cross-linking points may make the structure of carbon nanofibers loose. At the same time, the lack of sufficient cross-linking points will also affect the performance of carbon nanofibers in terms of electrical conductivity and thermal conductivity, limiting their application as high-performance materials in various fields. These problems make the performance of carbon nanofibers in practical applications unsatisfactory, and further research and improvement are urgently needed to improve their comprehensive performance so as to meet the requirements of use in various complex environments.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a carbon nanofiber aerogel and a preparation method thereof, aiming to solve the problems of weak mechanical properties and stability, and poor electrical conductivity and thermal conductivity of existing carbon aerogels.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing carbon nanofiber aerogel comprises the following steps:

[0008] Mixing a bacterial cellulose dispersion containing an inorganic ammonium salt with a polymer solution to obtain a mixed dispersion;

[0009] Freezing the mixed dispersion and freeze-drying the mixture to obtain bacterial cellulose aerogel;

[0010] The bacterial cellulose aerogel is subjected to pyrolysis treatment to obtain carbon nanofiber aerogel.

[0011] In the method for preparing the carbon nanofiber aerogel, the inorganic ammonium salt comprises one or more of ammonium chloride, ammonium sulfate, and diammonium phosphate.

[0012] The method for preparing the carbon nanofiber aerogel, wherein, in the bacterial cellulose dispersion containing the inorganic ammonium salt, the mass fraction of the inorganic ammonium salt relative to the bacterial cellulose is 0.5% to 80%.

[0013] In the method for preparing the carbon nanofiber aerogel, the polymer in the polymer solution includes one or more of glucose, sodium alginate, and chitosan.

[0014] In the method for preparing the carbon nanofiber aerogel, the mass fraction of the polymer solution relative to the bacterial cellulose is 0.5% to 40%.

[0015] In the method for preparing the carbon nanofiber aerogel, the freezing treatment is to place the mixed dispersion on a freezing table at -20°C to -60°C and freeze it for 10 minutes to 40 minutes.

[0016] The method for preparing the carbon nanofiber aerogel, wherein the temperature of the pyrolysis treatment is 600°C to 1400°C, the heating rate of the pyrolysis treatment is 2°C / min to 10°C / min, and the time of the pyrolysis treatment is 1h to 3h.

[0017] In the method for preparing the carbon nanofiber aerogel, the pyrolysis treatment is carried out under an inert atmosphere or under vacuum conditions.

[0018] A carbon nanofiber aerogel is prepared by using a method for preparing carbon nanofiber aerogel.

[0019] The carbon nanofiber aerogel has a density of 3 mg·cm -3 ~25mg·cm -3 .

[0020] Beneficial effects: The present invention provides a carbon nanofiber aerogel and a preparation method thereof. The preparation method of the carbon nanofiber aerogel comprises: mixing a bacterial cellulose dispersion containing an inorganic ammonium salt with a polymer solution to obtain a mixed dispersion; freezing the mixed dispersion to obtain a bacterial cellulose aerogel after freeze drying; and pyrolyzing the bacterial cellulose aerogel to obtain a carbon nanofiber aerogel. The present invention introduces a polymer in the process of preparing the carbon nanofiber aerogel, which can significantly increase the crosslinking density between carbon nanofibers by forming additional physical or chemical crosslinks in the structure of the carbon nanofiber aerogel, improve the structural stability of the carbon nanofiber aerogel, and effectively enhance its mechanical properties. In addition, the polymer chain connects the gaps between the carbon nanofibers, promotes the uniform distribution of stress, and reduces local stress concentration. In addition, the introduction of the polymer can also regulate the void structure of the aerogel and improve the thermal stability and conductivity of the material. The carbon nanofiber aerogel has a low density and a high volume retention rate, can provide a high specific surface area, and is conducive to the adsorption or catalytic reaction. The compression stress enhancement improves the mechanical stability of the carbon nanofiber aerogel, making it less likely to deform when subjected to external pressure. The carbon nanofiber aerogel obtained by the preparation method has a density of 3 to 25 mg cm -3 , volume retention rate is 15-50%, and maximum compression strength is >9KPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A schematic diagram of a process flow of a method for preparing carbon nanofiber aerogel according to the present invention;

[0022] Figure 2 This is a physical picture of the carbon nanofiber aerogel obtained in Example 1;

[0023] Figure 3 is a stress-strain curve of the carbon nanofiber aerogel obtained in Example 1 after 100 cycles at 60% compression strain;

[0024] Figure 4 This is a physical picture of the carbon nanofiber aerogel obtained in Example 2;

[0025] Figure 5 is the stress-strain curve of the carbon nanofiber aerogel obtained in Example 2 after 100 cycles at 60% compression strain;

[0026] Figure 6 This is a physical picture of the carbon nanofiber aerogel obtained in Example 3;

[0027] Figure 7 This is the stress-strain curve of the carbon nanofiber aerogel obtained in Example 3 after 100 cycles at 60% compressive strain. DETAILED DESCRIPTION

[0028] The present invention provides a carbon nanofiber aerogel and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0030] like Figure 1 As shown, the present invention provides a method for preparing carbon nanofiber aerogel, comprising the steps of:

[0031] Step S10: mixing the bacterial cellulose dispersion containing the inorganic ammonium salt with the polymer solution to obtain a mixed dispersion;

[0032] Step S20: freezing the mixed dispersion and freeze-drying it to obtain bacterial cellulose aerogel;

[0033] Step S30: performing pyrolysis treatment on the bacterial cellulose aerogel to obtain carbon nanofiber aerogel.

[0034] In this embodiment, a polymer is introduced during the preparation of the carbon nanofiber aerogel, which can significantly increase the crosslinking density between the carbon nanofibers by forming additional physical or chemical crosslinks in the structure of the carbon nanofiber aerogel, improve the structural stability of the carbon nanofiber aerogel, and effectively enhance its mechanical properties. In addition, the polymer chain connects the gaps between the carbon nanofibers, promotes the uniform distribution of stress, and reduces local stress concentration. In addition, the introduction of the polymer can also regulate the void structure of the aerogel and improve the thermal stability and electrical conductivity of the material. The carbon nanofiber aerogel has a low density and a high volume retention rate, and can provide a high specific surface area, which is conducive to the adsorption or catalytic reaction. The compression stress enhancement improves the mechanical stability of the carbon nanofiber aerogel, making it less likely to deform when subjected to external pressure. And the density of the carbon nanofiber aerogel obtained by the preparation method is 3 to 25 mg cm -3 , the volume retention rate is 15-50%, and the maximum compression strength is greater than 9KPa; and the present invention uses bacterial cellulose and common polymers as precursors, the raw materials are cheap and easily available, the method is simple, and it is easy to produce on a large scale.

[0035] Specifically, the carbon nanofiber aerogel of the present invention is prepared by carbonization of bacterial cellulose, which is a highly ordered nanofiber structure. The carbonization process can convert it into carbon nanofibers. This transformation greatly reduces the density of the material while retaining the network structure of the nanofibers; however, due to the high-temperature decomposition of organic matter during the carbonization process, the material will experience volume shrinkage, resulting in a decrease in volume retention rate. In the pyrolysis process, inorganic salts act as a catalyst, which effectively promotes the dehydration of bacterial cellulose fibers by changing the pyrolysis mode of bacterial cellulose fibers and changing the pyrolysis route, so that the carbon-oxygen ratio in the escaped gaseous and liquid products decreases, and the carbon residue after pyrolysis of bacterial cellulose is increased; the polymer introduced in the preparation process of the present invention can produce additional carbon during the carbonization process, so that the connection between carbon nanofibers is tighter and the overall structural strength of the material is enhanced. This composite carbon network formed by the carbonization of the polymer not only increases the carbon content of the aerogel, but also further improves the mechanical properties of the aerogel through crosslinking and filling. The high-strength carbon network can better disperse stress and avoid structural collapse or excessive deformation when subjected to external forces, thereby significantly improving the maximum compressive strength of the aerogel.

[0036] In some embodiments, the inorganic ammonium salt includes one or more of ammonium chloride, ammonium sulfate, and ammonium dihydrogen phosphate. The above inorganic ammonium salt is used as a catalyst, which can change the pyrolysis mode of bacterial cellulose fiber, change the pyrolysis route, effectively promote the dehydration of bacterial cellulose fiber, reduce the carbon-oxygen ratio in the escaped gaseous and liquid products, and increase the carbon residue after pyrolysis of bacterial cellulose.

[0037] In some embodiments, the mass fraction of the inorganic ammonium salt relative to the bacterial cellulose in the bacterial cellulose dispersion containing the inorganic ammonium salt is 0.5% to 80%. Controlling the mass fraction of the inorganic ammonium salt within the above range enables the polymer solution to effectively wrap the bacterial fibers, forms new cross-linking points after carbonization, and increases the amount of carbon residue after pyrolysis of the bacterial cellulose.

[0038] In a preferred embodiment, in the bacterial cellulose dispersion containing inorganic ammonium salt, the mass fraction of inorganic ammonium salt relative to bacterial cellulose is 0.5% to 60%, more preferably 0.5 to 50%, and most preferably 0.5 to 40%; in some embodiments provided by the present invention, the mass fraction of diammonium phosphate relative to bacterial cellulose is preferably 17%.

[0039] In some embodiments, in the bacterial cellulose dispersion containing inorganic ammonium salt, the mass fraction of inorganic ammonium salt relative to bacterial cellulose is 0.8%-50%.

[0040] In some embodiments, the polymer in the polymer solution includes one or more of glucose, sodium alginate, and chitosan. The introduction of the above polymers can also regulate the void structure of the aerogel and improve the thermal stability and conductivity of the material. Preferably, the solvent of the polymer solution is only deionized water.

[0041] In some embodiments, the mass fraction of the polymer solution relative to the bacterial cellulose is 0.5% to 40%. Controlling the mass fraction of the polymer solution within the above range can effectively wrap the BC fibers with the polymer solution, form new cross-linking points after carbonization, and allow the polymer to form polymer chains in the carbon nanofiber aerogel, connect the gaps between the carbon nanofibers, promote uniform distribution of stress, and reduce local stress concentration.

[0042] In some embodiments, the freezing treatment is to place the mixed dispersion on a freezing table at -20°C to -60°C for 10 to 40 minutes. The mixed dispersion can be frozen to form ice cubes; then, the water in the ice cubes can be sublimated and removed after freeze drying under vacuum low temperature conditions, and the freeze-dried aerogel forms a honeycomb pore structure.

[0043] It should be explained that the term "freezing" refers to the process of converting the dispersion of bacterial cellulose and polymer into ice cubes; and the term "freeze drying" refers to placing these frozen ice cubes in a freeze dryer and drying them through a sublimation process in a low-temperature vacuum environment.

[0044] In a preferred embodiment, the temperature of the freezing table is -30°C to -40°C, and the time is preferably 20min to 30min.

[0045] In some embodiments, the freeze-drying time is 3 to 5 days, so that the water in the ice cubes is completely sublimated to obtain an anhydrous honeycomb porous structure aerogel.

[0046] Specifically, the mixed dispersion is poured into a container, placed on a freezing table at -20 to -60°C to freeze, and then freeze-dried to obtain bacterial cellulose aerogel. Freezing at a specified temperature can fully freeze the bacterial cellulose dispersion and have an orderly internal structure. If the temperature is too high or too low, the extrusion of crystals during the freezing process will cause the internal pores of the bacterial cellulose to become larger. Completing the freeze-drying step within a specified time can completely dry the bacterial cellulose aerogel.

[0047] In some embodiments, the temperature of the pyrolysis treatment is 600° C. to 1400° C., the heating rate of the pyrolysis treatment is 2° C. / min to 10° C. / min, and the time of the pyrolysis treatment is 1 hour to 3 hours. Under this condition, the pyrolysis treatment can convert the BC fibers into carbon nanofibers, and the pyrolysis within this temperature range can convert the BC fibers into carbon nanofibers as completely as possible.

[0048] Specifically, the bacterial cellulose aerogel is preferably placed in a ceramic boat for pyrolysis treatment; the pyrolysis treatment is preferably carried out in a tubular furnace; the heating rate of the pyrolysis treatment is preferably 3-8°C / min, more preferably 4-6°C / min, and most preferably 5°C / min; the temperature of the pyrolysis treatment is preferably 800°C-1200°C; the time of the high-temperature pyrolysis is preferably 1-3h, that is, after heating to the high-temperature pyrolysis temperature, keeping warm for 1-3h, more preferably 2h.

[0049] In some embodiments, after the pyrolysis treatment, a staged cooling is adopted; specifically: after the pyrolysis treatment, the temperature is preferably cooled to 400°C to 600°C, more preferably to 450°C to 550°C, and then preferably to 500°C, and then naturally cooled to room temperature to obtain carbon nanofiber aerogel; the cooling rate is preferably 4 to 6°C / min, more preferably 5°C / min. In this embodiment, during the pyrolysis treatment and the cooling process, the tubular furnace is kept at normal pressure.

[0050] In some embodiments, the pyrolysis treatment is performed under an inert atmosphere or under vacuum conditions. The inert atmosphere can be any protective atmosphere known to those skilled in the art, and in this embodiment, nitrogen or argon is preferred.

[0051] In some embodiments, the carbon nanofiber aerogel is in a regular block shape with a length of 5 to 50 mm, a width of 5 to 50 mm and a thickness of 5 to 30 mm, and the nanofibers inside are interwoven to form a highly cross-linked three-dimensional network structure.

[0052] In a preferred embodiment, the bacterial cellulose aerogel is (20-25)×(20-25)×(17-20) mm 3 The carbon nanofiber aerogel obtained after pyrolysis in step S30 is (13-18)×(13-18)×(12-15) mm 3 The volume retention rate is 15-50%.

[0053] In addition, the present invention also provides a carbon nanofiber aerogel, which is prepared by the preparation method of the carbon nanofiber aerogel.

[0054] In this embodiment, the carbon nanofiber aerogel is prepared by carbonization of bacterial cellulose, which is a highly ordered nanofiber structure. The carbonization process can convert it into carbon nanofibers. This transformation greatly reduces the density of the material while retaining the network structure of the nanofibers; however, due to the high-temperature decomposition of organic matter during the carbonization process, the material will experience volume shrinkage, resulting in a decrease in volume retention rate. In the pyrolysis process, inorganic salts act as a catalyst, by changing the pyrolysis mode of bacterial cellulose fibers, changing the pyrolysis route, effectively promoting the dehydration of bacterial cellulose fibers, reducing the carbon-oxygen ratio in the escaped gaseous and liquid products, and increasing the carbon residue after pyrolysis of bacterial cellulose; the polymer introduced in the preparation process of the present invention can produce additional carbon during the carbonization process, making the connection between carbon nanofibers more compact, and enhancing the overall structural strength of the material. This composite carbon network formed by the carbonization of the polymer not only increases the carbon content of the aerogel, but also further improves the mechanical properties of the aerogel through crosslinking and filling. The high-strength carbon network can better disperse stress, avoid structural collapse or excessive deformation when subjected to external forces, thereby significantly improving the maximum compressive strength of the aerogel.

[0055] In some embodiments, the density of the carbon nanofiber aerogel is 3 mg·cm -3 ~25mg·cm -3 .

[0056] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0057] Example 1

[0058] Add 0.016g of ammonium dihydrogen phosphate to 10g of 0.8% bacterial cellulose dispersion, shake thoroughly, then add 0.37g of 2.4% glucose solution, shake again to mix evenly. Use a vacuum oven to remove bubbles in the dispersion. Pour the resulting dispersion into a 25mm×25mm×20mm polytetrafluoroethylene mold and freeze it on a -40℃ freezer for 30 minutes. After complete freezing, transfer it to a freeze dryer and dry it for 3 days. The cold trap temperature is -60℃ and the pressure is 0.04mbar to obtain a bacterial cellulose / glucose mixed aerogel.

[0059] The bacterial cellulose / glucose mixed aerogel obtained by freeze drying was placed in a ceramic boat and then placed in a tubular furnace. Nitrogen was introduced into the tubular furnace as a protective gas. The tubular furnace was first heated to 1000°C at a rate of 5°C / min and maintained for 2 hours. The temperature was then cooled to 500°C at a rate of 5°C / min and finally naturally cooled to room temperature to obtain a black carbon nanofiber aerogel. The volume retention rate of the carbon nanofiber aerogel was 34%. Figure 2 The size of the obtained carbon nanofiber aerogel is 16 mm long × 16 mm wide × 13 mm thick. 3 , density is 7.3mg / cm 3 .

[0060] The carbon nanofiber aerogel obtained in Example 1 was subjected to mechanical testing. Figure 3 The stress-strain curve of the carbon nanofiber aerogel provided in this embodiment after 100 cycles at 60% compression strain. Since the pore structure of the carbon aerogel is stable and evenly distributed, the aerogel can still recover to its original shape after 100 compression cycles, indicating that it has good compression resilience.

[0061] Example 2

[0062] Add 0.016g of ammonium dihydrogen phosphate to 10g of 0.8% bacterial cellulose dispersion, shake thoroughly, then add 0.175g of 2.4% sodium alginate solution, shake again and mix evenly. Use a vacuum oven to remove bubbles in the dispersion. Pour the resulting dispersion into a 25mm×25mm×20mm polytetrafluoroethylene mold and freeze it on a -30℃ freezer for 25 minutes. After complete freezing, transfer it to a freeze dryer and dry it for 3 days. The cold trap temperature is -60℃ and the pressure is 0.04mbar to obtain a bacterial cellulose / sodium alginate mixed aerogel.

[0063] The bacterial cellulose / sodium alginate mixed aerogel obtained by freeze drying was placed in a ceramic boat and then placed in a tubular furnace; argon gas was introduced into the tubular furnace as a protective gas, and the tubular furnace was first heated to 1000°C at a rate of 5°C / min and maintained for 2 hours; then the temperature was lowered to 500°C at a rate of 5°C / min, and finally naturally cooled to room temperature to obtain a black carbon nanofiber aerogel with a volume retention rate of 33%. Figure 4 The size of the obtained carbon nanofiber aerogel is 15 mm long, 15 mm wide, and 12 mm thick. 3 , density is 7.85mg / cm 3 .

[0064] The carbon nanofiber aerogel obtained in Example 1 was subjected to mechanical testing. Figure 5The stress-strain curve of the carbon nanofiber aerogel provided in this embodiment after 100 cycles at 60% compression strain. Since the pore structure of the carbon aerogel is stable and evenly distributed, the aerogel can still recover to its original shape after 100 compression cycles, indicating that it has good compression resilience.

[0065] Example 3

[0066] Add 0.016g of ammonium dihydrogen phosphate to 10g of 0.8% bacterial cellulose dispersion, shake thoroughly, then add 0.37g of 2.4% chitosan solution, shake again and mix evenly. Use a vacuum oven to remove bubbles in the dispersion. Pour the resulting dispersion into a 15mm×15mm×15mm polytetrafluoroethylene mold and freeze it on a -40℃ freezer for 35min. After complete freezing, transfer it to a freeze dryer and dry it for 3 days. The cold trap temperature is -60℃ and the pressure is 0.04mbar to obtain a bacterial cellulose / glucose mixed aerogel.

[0067] The bacterial cellulose / glucose mixed aerogel obtained by freeze drying was placed in a ceramic boat and then placed in a tubular furnace; the tubular furnace was vacuumed, first the tubular furnace was heated to 1000°C at a rate of 5°C / min and maintained for 2h; then the temperature was lowered to 500°C at a rate of 5°C / min and finally naturally cooled to room temperature to obtain a black carbon nanofiber aerogel with a volume retention rate of 20%. Figure 6 The size of the obtained carbon nanofiber aerogel is 8mm in length, 8mm in width, and 9mm in thickness. 3 , density is 9.9mg / cm 3 .

[0068] The carbon nanofiber aerogel obtained in Example 1 was subjected to mechanical testing. Figure 7 The stress-strain curve of the carbon nanofiber aerogel provided in this embodiment after 100 cycles at 60% compression strain. Since the pore structure of the carbon aerogel is stable and evenly distributed, the aerogel can still recover to its original shape after 100 compression cycles, indicating that it has good compression resilience.

[0069] In summary, the present invention provides a carbon nanofiber aerogel and a preparation method thereof, and the preparation method of the carbon nanofiber aerogel comprises: mixing a bacterial cellulose dispersion containing an inorganic ammonium salt with a polymer solution to obtain a mixed dispersion; freezing the mixed dispersion, and obtaining a bacterial cellulose aerogel after freeze drying; pyrolyzing the bacterial cellulose aerogel to obtain a carbon nanofiber aerogel. The present invention introduces a polymer in the process of preparing the carbon nanofiber aerogel, which can significantly increase the crosslinking density between the carbon nanofibers by forming additional physical or chemical crosslinks in the structure of the carbon nanofiber aerogel, improve the structural stability of the carbon nanofiber aerogel, and effectively enhance its mechanical properties. In addition, the polymer chain connects the gaps between the carbon nanofibers, promotes the uniform distribution of stress, and reduces local stress concentration. In addition, the introduction of the polymer can also regulate the void structure of the aerogel, and improve the thermal stability and conductivity of the material. The carbon nanofiber aerogel has a low density and a high volume retention rate, can provide a high specific surface area, and is conducive to the adsorption or catalytic reaction. The compression stress enhancement improves the mechanical stability of the carbon nanofiber aerogel, making it less likely to deform when subjected to external pressure. The carbon nanofiber aerogel obtained by the preparation method has a density of 3 to 25 mg cm -3 , volume retention rate is 15-50%, and maximum compression strength is >9KPa.

[0070] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing carbon nanofiber aerogel, characterized in that: Includes steps: Mixing a bacterial cellulose dispersion containing an inorganic ammonium salt with a polymer solution to obtain a mixed dispersion; Freezing the mixed dispersion and freeze-drying the mixture to obtain bacterial cellulose aerogel; The bacterial cellulose aerogel is subjected to pyrolysis treatment to obtain carbon nanofiber aerogel.

2. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: The inorganic ammonium salt includes one or more of ammonium chloride, ammonium sulfate, and diammonium phosphate.

3. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: In the bacterial cellulose dispersion containing inorganic ammonium salt, the mass fraction of the inorganic ammonium salt relative to the bacterial cellulose is 0.5% to 80%.

4. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: The polymer in the polymer solution includes one or more of glucose, sodium alginate and chitosan.

5. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: The mass fraction of the polymer solution relative to the bacterial cellulose is 0.5% to 40%.

6. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: The freezing treatment is to place the mixed dispersion on a freezing table at -20°C to -60°C and freeze it for 10 minutes to 40 minutes.

7. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: The temperature of the pyrolysis treatment is 600° C. to 1400° C., the heating rate of the pyrolysis treatment is 2° C. / min to 10° C. / min, and the time of the pyrolysis treatment is 1 h to 3 h.

8. The method for preparing carbon nanofiber aerogel according to claim 1, characterized in that: The pyrolysis treatment is carried out under an inert atmosphere or under a vacuum condition.

9. A carbon nanofiber aerogel, characterized in that: The carbon nanofiber aerogel is prepared by the method for preparing the carbon nanofiber aerogel according to any one of claims 1 to 8.

10. The carbon nanofiber aerogel according to claim 9, characterized in that: The density of the carbon nanofiber aerogel is 3 mg cm -3 ~25mg·cm -3 .

Citation Information

Patent Citations

  • Bacterial cellulose-derived carbon nanofiber aerogel and preparation method thereof

    CN107265438A

  • Method for preparing lithium-sulfur battery cathode material by using bacterial cellulose hydrogel

    CN109962222A

  • Carbon nanofiber aerogel chunk and preparation method thereof

    CN110117000A

  • Preparation method for lithium sulfide self-supporting carbon sphere / carbon nanofiber composite material, and lithium-sulfur battery

    CN110212180A

  • Magnetic aerogel based on diamidoxime cellulose / sodium alginate, and preparation and application thereof

    CN110229383A

Cited By

  • Carbon-silicon carbide nanofiber aerogel with 3D core-shell structure and preparation method of carbon-silicon carbide nanofiber aerogel

    CN121046993A